The Mechanism of Newsroom and TV Journalist Work Routines during the COVID-19 Pandemic - Musfialdy, Musfialdy; Hidayat, Dadang Rahmat; Karlinah, Siti; Wahyudin, Uud; Jamal, Muchamad Fauzi (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2024)
A disease outbreak known as COVID-19 (Corona Virus Diseases 2019) is currently affecting virtually every part of the planet. The COVID-19 outbreak is a catastrophe that endangers and disrupts life, causes fatalities, traumatizes victims, and engenders a climate of threat and fear. The COVID-19 pandemic tragedy not only affected the number of sick and deceased individuals but also altered work schedules in the neighborhood. Additionally, COVID-19 has brought about changes in journalism, particularly in television journalism. The purpose of this study is to ascertain the mechanism governing the operational procedures of newsroom and television journalism during the COVID-19 pandemic. Expectancy Violation Theory and Judee K. Burgoon’s Interaction Adaptation Theory were both used in this study. This research approach employed a constructive subjective paradigm and utilized a qualitative case study methodology. The subjects of this study were the journalists and editors of iNews TV and Metro TV. The study’s finding show that the COVID-19 pandemic has impacted how journalists work both in the workplace and in the field, causing disruption and changes to their routines. Nevertheless, the pandemic has also prompted an acceleration of the process of adapting how journalistic tasks are carried out, both in the newsroom and on the ground. Despite the acceleration, the COVID-19 epidemic has expedited the process of adaptation and adjustment. Finally, the transformation has resulted in new business strategies in the television industry due to the COVID-19 pandemic.